Microporella hastingsae Harmelin, Ostrovsky, Cáceres-Chamizo and Sanner, 2011 (Bryozoa, Cheilostomatida): a possible new Lessepsian species in the Mediterranean Sea? - ROSSO, ANTONIETTA; SIDDIOLO, CHIARA (Mediterranean Marine Science, 2024)
The introduction of Non-Indigenous Species (NIS) in the Mediterranean Sea is one of the main threats to biodiversity and its increasing frequency could bring a significant ecological impact on native species. However, knowledge of marine bioinvasions, the spreading patterns of NIS and their possible pathways of dispersion is still limited, especially for particular taxonomic groups. In this paper, we report the first Mediterranean record of a colony of a non-indigenous bryozoan, Microporella hastingsae Harmelin, Ostrovsky, Cáceres-Chamizo and Sanner, 2011, found on plastic litter stranded south of Catania (Sicily, western Ionian Sea) during spring 2023. Based on this colony, a formal taxonomic description of M. hastingsae is provided for this species, which was recently erected for old, misidentified material collected in the early twentieth century in the Suez Canal and the north Red Sea. We suggest that the species could be considered a Lessepsian migrant assuming it entered the Mediterranean Sea at any time, through larval dispersal and/or the possible facilitation by human activities, presumably shipping. Further surveys in coastal localities of Sicily and the eastern Mediterranean are needed to confirm the establishment of M. hastingsae or if the present colony only represents an occasional record of the species in the basin.